Incidence and mortality of kidney cancer: temporal patterns and global trends in 39 countries. Issue 1 (December 2017) - Wong, Martin; Goggins, William; Yip, Benjamin; Fung, Franklin; Leung, Colette; Fang, Yuan; Wong, Samuel; Ng, C.
Abstract We tested the hypotheses that kidney cancer incidence was increasing globally whilst its mortality was reducing; and its incidence was positively correlated with country-specific socioeconomic development. The incidence and mortality figures of each country were projected to 2030. Data on age-standardized incidence/mortality rates were retrieved from the GLOBOCAN in 2012. Temporal patterns were examined for 39 countries from the Cancer Incidence in Five Continents volumes I-X and other national registries. We evaluated the correlation between the incidence/mortality rates and Human Development Index (HDI)/Gross Domestic Product (GDP]). The average annual percent change of its incidence and mortality in the most recent 10 years was obtained from joinpoint regression. The highest incidence rates were observed in Eastern Europe and North America, while its mortality rates were the highest in European countries. Incidence was positively correlated with HDI and GDP per capita. Many countries experienced incidence rise over the most recent 10 years, and a substantial reduction in mortality rates was observed for a significant number of countries, yet increases in mortality rates were observed in Eastern Europe. By 2030, Brazil and Ecuador may have the greatest rise in incidence both in men and women, which requires urgent need for planning healthcare resources.